Application of GIS Technology in OSS/BSS - Zhi Sun; Ling Li; Shizhe Liu (Dianxin kexue)
GIS technology can be used for all the services about spatial location,to improve the service efficiency and service quality of the OSS/BSS.The GIS technology development trend and OSS/BSS principle were introduced,the various applications of GIS technology in the OSS/BSS were summarized,the problems and evolutions in the GIS platform of telecommunications were analyzed,and GIS future trends forecast was made.